Challenges for Catholic schools in contemporary Uruguay. Issue 1 (2nd January 2020) - Aristimuño, Adriana
Abstract : This article reviews and updates a previous work published in 2007 as a chapter in the International Handbook of Catholic Education (Aristimuño, A. 2007. "Challenges for Catholic Schools in Uruguay." In International Handbook of Catholic Education: Challenges for School Systems in the 21st Century. Part One, edited by Gerald Grace and S. J. Joseph O'Keefe, 149–163, Dordrecht: Springer). Its purpose is to review and analyze the transformations Catholic education has experienced since then in the small and secularised country of Uruguay, and by doing so, to identify its main contemporary challenges. It incorporates new literature and findings related to Catholic education globally (Grace, G. 2016. Faith, Mission and Challenge in Catholic Education . The Selected Works of Gerald Grace . London: Routledge; Lydon, J. 2009. "Transmission of the Charism: A Major Challenge for Catholic Education." International Studies in Catholic Education 1 (1): 42–58), to new ways of religion that are growing in Latin America (Da Costa, N. 2017. "Creencias y descreencias desde las experiencias cotidianas. Una mirada desde Uruguay." Estudos de Religiao 31 (3): 1–21; Morello, G. et al. 2017. "Lived Religion in Latin America and Europe. The Roman-Catholic Experience in Everyday Life." Quaderni del Csal-4, Centro Studi per l'America Latina, IX (17). Trieste: Edizione Universita di Trieste), new empirical research about the current situation of Catholic education in the country (Census AUDEC, 2016 and 2017), and the voice of several new Catholic education leaders who run influential educational organisations in the country. These new sources and findings show that in spite of some demanding social and global changes, what sustains and inspires the work of the protagonists at the heart of Catholic education in Uruguay continues to be its 'spiritual capital', defined as 'resources of faith and values derived from commitment to a religious tradition' (Grace, G. 2002. Catholic Schools: Mission, Markets and Morality . London: Routledge Falmer, p. 236).